Mitochondrial abnormalities in the myofibrillar myopathies. (23rd July 2015) - Jackson, S.; Schaefer, J.; Meinhardt, M.; Reichmann, H.
<x xml:space="preserve">Abstract</x> Myofibrillar myopathies are a genetically diverse group of skeletal muscle disorders, with distinctive muscle histopathology. Causative mutations have been identified in the genes MYOT, LDB3, DES, CRYAB, FLNC, BAG3, DNAJB6, FHL1, PLEC and TTN, which encode proteins which either reside in the Z‐disc or associate with the Z‐disc. Mitochondrial abnormalities have been described in muscle from patients with a myofibrillar myopathy. We reviewed the literature to determine the extent of mitochondrial dysfunction in each of the myofibrillar myopathy subtypes. Abnormal mitochondrial distribution is a frequent finding in each of the subtypes, but a high frequency of COX‐negative or ragged red fibres, a characteristic finding in some of the conventional mitochondrial myopathies, is a rare finding. Few in vitro studies of mitochondrial function have been performed in affected patients.